A promoção da igualdade racial e a política pública de formação dos professores da Educação Infantil em Belo Horizonte - Lisa Minelli Feital (2016)
The dissertation was developed with the objective of discussing aspects of Politician national and local public policies to promote racial equality and reflect on the actions of continuing education developed for different levels of the Municipal Department of Education MDE together to the Basic Education teachers in day care centers with Hall of Belo Horizonte HBH in Municipal Units of Childhood Education MUCEs in the city. We asked first to what extent the municipal school system has offered conditions for the teachers of the childhoodeducation see themselves as subjects protagonists of promoting implementation process protagonists of the implementation process of promoting racial equality in spaces and institutional times with reference the Law 10.639 / 03, which provides, among other things, theinclusion in the curriculum educational institutions working with the history and culture the African people. We adopted as methodological strategies to literature review, document analysis and carrying out semi-structured interviews with teachers and managers involved and/ or responsible directly by the continuing education activities in the childhood education. Data analysis came from a qualitative approach. As a result we found that the Racial-Ethnic Relations Center, Early Childhood Education Coordination Management ECECM and pedagogical teams of Managements of Education - MEs - of Belo Horizonte develop regional meetings, seminars, meetings and workshops, among other activities, with teachers that are defined bymanagers as continuing education actions, but which are not always understood by teachers that way. In addition, we have identified that there is a recognition among participants the research that the theme of promoting racial equality has advanced in the city but still needs tobe taken with main hub for training policies of the teachers of Education